A genome-wide association study identifies candidate genes for target leaf spot disease resistance in adult cucumber (Cucumis sativus L.) - Xu, Ying’ao; Dong, Shaoyun; Xie, Xuewen; Beckles, Diane M.; Liu, Xiaoping; Guan, Jiantao; Li, Caixia; Gu, Xingfang; Miao, Han; Zhang, Shengping (Frontiers in Plant Science, 2025)
Target leaf spot disease (TLS), caused by Corynespora cassiicola (Berk & Curt) Wei, ranks among the most serious fungal diseases affecting cucumber production. However, the genetic basis for TLS resistance in cucumber has not yet been determined. In this study, we evaluated TLS resistance in the adult plants of 130 cucumber accessions using a disease index (DI) in October 2021, June 2023, and October 2023. The accessions used in this study were representative collection selected from the global 3,342 accessions, and contain four ecotypes (the Eurasian, Indian, East Asian, and Xishuangbanna type). Cluster analysis suggested that 11 of the 130 accessions exhibited high levels of TLS resistance (CG28, CG70, CG84, CG86, CG100, CG104, CG98, R163, R61, CG64, CG71). A genome-wide association study (GWAS) analysis was then performed based on the BLUP value of the DI collected from these three seasons, and three loci (gTLS5.1, gTLS5.2, and gTLS7.1) associated with TLS on two chromosomes were identified. Seven candidate genes linked to disease resistance and abiotic stress were identified through functional annotation with Arabidopsis orthologous genes and pairwise linkage disequilibrium (LD) correlation analysis. Sequence alignment, expression and haplotype analysis further indicated to five of these candidate genes as being potentially causal to TLS: CsaV3_5G010580 for gTLS5.1, and CsaV3_7G026140, CsaV3_7G026180, CsaV3_7G026200 and CsaV3_7G026220 for gTLS7.1. These genes related to TLS resistance in cucumber, could be useful to promote cucumber breeding and development.